Confocal micro-flow visualization of blood cells - Lima, R. (2011)
Progress in the development of confocal microscopy and the advantages of this technique over conventional microscopy have led to a new technique known as confocal micro-PTV. This technique combines a manual tracking method with a spinning disk confocal microscope. By combining its spatial filtering technique with a multipoint illumination system, this technique has the ability to obtain in-focus images with optical thickness less than 5 mm. The present study shows the ability of our confocal micro-PTV system to obtain detailed qualitative and quantitative information on the blood flow behavior in both glass capillaries and polydimethylsiloxane(PDMS) microchannels. By labeling the blood cells with a lipophilic carbocyanime derivative it was possible to measure both translational and rotational motion occurring during flow. Our results demonstrate the ability of our confocal micro-PTV system to obtain both translational and rotational motion of individual RBCs flowing in concentrated suspensions. Owing to its optical sectioning ability and consequent improvement of the image contrast and definition, the proposed confocal system can provide additional detailed description on the blood cells motion not obtainable by other conventional methods.